2013
DOI: 10.1002/ar.22751
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis of the Extra‐Bulbar Olfactory Pathway in Xenopus laevis

Abstract: Although the development, anatomy, and physiology of the vertebrate olfactory system are fairly well understood, there is still no clear definition of the terminal nerve complex acknowledged by all. Among the most debated matters is whether or not the extrabulbar projections found in anamniotes should or should not be considered part of the terminal nerve complex. In this context, we investigated the early development of the extrabulbar pathway in Xenopus larvae from placodal differentiation to postmetamorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, in the medial amygdala a co-innervation of main and accessory projection neurons is present indicating a convergence and integration of the information of these two systems at this level (Scalia et al 1991b ; Moreno and González 2003 ). It is also notable that some extrabulbar fibers originating from the OE project to deeper diencephalic brain regions by bypassing the OB (Hofmann and Meyer 1992 ; Pinelli et al 2004 ; D’aniello et al 2008 ; Gaudin et al 2013 ). Functional evidence about processing of olfactory information in higher olfactory centers is scarce and it is unknown how olfactory information from sensory epithelia for water or air is integrated.…”
Section: The Anuran Olfactory Systemmentioning
confidence: 99%
“…Interestingly, in the medial amygdala a co-innervation of main and accessory projection neurons is present indicating a convergence and integration of the information of these two systems at this level (Scalia et al 1991b ; Moreno and González 2003 ). It is also notable that some extrabulbar fibers originating from the OE project to deeper diencephalic brain regions by bypassing the OB (Hofmann and Meyer 1992 ; Pinelli et al 2004 ; D’aniello et al 2008 ; Gaudin et al 2013 ). Functional evidence about processing of olfactory information in higher olfactory centers is scarce and it is unknown how olfactory information from sensory epithelia for water or air is integrated.…”
Section: The Anuran Olfactory Systemmentioning
confidence: 99%
“…The use of lipophilic tracers as well as biocytin as a tracer has been successfully assessed to visualize extrabulbar primary olfactory projections (EBOP) in actinopterygians (Anadón et al, ; Folgueira et al, ; Gayoso et al, ; Holmqvist et al, ; Huesa et al, ; Northcutt, ) and amphibians (D'Aniello et al, ; Gaudin and Gascuel, ; Gaudin et al, ; Pinelli et al, ). In the present study, the results of the distribution of primary olfactory fibers obtained from biocytin application to the nostril were generally similar to those obtained after lipophilic tracers application, but the number and extent of fibers was sometimes less conspicuous compared with the latter procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These fibers bypass the olfactory bulbs (OBs) and reach different brain regions. Such a fiber system has been demonstrated in cyclostomes, (Meyer et al, ; Northcutt and Puzdrowski ; von Bartheld and Meyer ; von Bartheld et al, ), bony fishes (Anadón et al, ; Bazer et al, ; Becerra et al, ; Castro et al, ; Demski and Northcutt, ; Folgueira et al, ; Gayoso et al, ; Hofmann and Meyer, ; Holmqvist et al, ; Honkanen and Ekström, ; Huesa et al, ; Northcutt, ; Riddle and Oakley, ; Szabo et al, ; von Bartheld and Meyer, ) and amphibians (D'Aniello et al, ; Gaudin et al, ; Hofmann and Meyer, ,b, 1991a,b; Meyer et al, ; Pinelli et al, ; Schmidt and Wake, ; Schmidt et al, ). Strikingly, extrabulbar primary olfactory fibers have not yet been described in elasmobranchs (Dryer and Graziadei, ; Hofmann and Meyer, ; Yàñez et al, ), while they have been reported in endotherm vertebrates: embryonic (Santacana et al, ) and adult rats (Monti‐Graziadei, ), and ducklings (Meyer et al, ; von Bartheld et al, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many interesting studies on development and evolution—they are often tightly linked in comparative anatomical studies—appeared in the following years in The Anatomical Record . Included in these are: developmental and descriptive studies of the facial nerve in humans and trigeminal nerve (CN V) in baboons by noted embryologist and consummate teacher of embryology, Raymond Gasser (Gasser, ; Gasser and Wise, ) of Louisiana State University School of Medicine (Ray's southern warmth, hearty laugh, and gregariousness was a mainstay at anatomical meetings worldwide); Easter's meticulous study (Easter, ) of the growth and development of the trochlear nerve (CN IV) and superior oblique muscle in goldfish; Brown's () study of the Nervus terminalis in embryos of insectivorous bats; Kitamura et al detailed, anatomical studies on rabbit vagus (CN X) and spinal accessory nerves (CN XI) and their nuclei and pharyngeal constrictor muscle innervations, and implications for understanding the history of the complex (Kitamura et al, , , ); Kalmey et al’s study on age‐related size reduction in the foramina of the cribriform plate and effects upon reduction in olfactory nerve (CN I) function in the elderly (Kalmey et al, ); Butler's excellent review and synthesis of chordate head and brain evolution (Butler, ); Diaz et al’s detailed review on the olfactory system sensu lato (Diaz et al, ); Gaudin et al’s study on the ontogenetic development of the extra‐bulbar olfactory pathway in xenopus (Gaudin et al, ; Wohlert et al, ) morphometric study of the axonal number differences in optic, trigeminal and vestibulocochlear nerves among seals as a means to gain insight into their functional differences and relationships; and last, but never least, a report by the great polymath, frequent contributor to The Anatomical Record , and one of our favorite Canadian anatomists (eh! ), A. Wayne Vogl of beautiful University of British Columbia, on the functional anatomy of nerves innervating the grooved blubber of fin whales (Vogl et al, ).…”
mentioning
confidence: 99%